"I Want to Do It, But I Want to Make Sure That I Do It Right." Views of Patients with Parkinson's Disease Regarding Early Stem Cell Clinical Trial Participation. Issue 3 (2nd July 2020) - de Melo-Martín, Inmaculada; Holtzman, Michael; Hacker, Katrina S.
Abstract: Background : First-in-human clinical trials with stem cells for Parkinson's disease (PD) are on the horizon. Their epistemic success depends on ensuring the participation of a sufficient number and appropriately diverse group of patients with PD. Their ethical soundness requires that the research community ensures that subjects' decisions about whether to participate or not are consistent with participants' values, motivations, and goals. We sought to identify PD patients' knowledge, concerns, and expectations regarding early-phase stem cell research in PD. Methods : We conducted five semi-structured focus groups with patients with PD. Group discussions were recorded, transcribed, and coded to identify participants' knowledge, concerns, and expectations regarding participation in early stem cell clinical research in PD. Results : Four themes were generated from our data analysis: (1) participants' skepticism about the potential benefits of these trials; (2) their desire to obtain information about various aspects related to this research; (3) a recognition that accessing available knowledge was often difficult; and (4) the relevance of trusting relationships with various stakeholders. Conclusions : Participants expressed skepticism about the immediate impact of stem cell research. Nonetheless, such skepticism often reflected an appropriate consideration of the risks and potential benefits of participating in high-risk clinical trials. Despite their skepticism, participants were eager to learn more about stem cell research and clinical trials processes. They identified consistently trusted avenues of knowledge on these topics, but they often found it difficult to access relevant information or to determine its value.